A 9-GHz 65-nm Intel® Pentium 4 Processor Integer Execution Unit. - Wijeratne, S. B.
This paper describes a fourth generation Intel Pentium 4 processor integer execution core operating at 9 GHz in a 1.3-V, 65-nm CMOS technology at 70degC. Low-voltage-swing circuits of the 90-nm design are replaced by: 1) 2times frequency fast clock (FCLK)-optimized domino clocking scheme; 2) segmented arithmetic and logic unit (ALU) front-end multiplexer; 3) sparse-tree ALU adder; 4) merged add/subtract sparse-tree address generation unit (AGU) design; 5) speculative RC-delay-optimized rotator; and 6) single-rail L0 cache and alignment multiplexer, resulting in 8.4% reduction in integer core normalized active power and 42% reduction in normalized leakage power. The use of standard domino/static tools and methodologies lowers design complexity, reducing development cost and time. The redesign also reduces integer core thermal density, resulting in an 8degC reduction in CPU operating temperature
Keywords: 1.3 V; 65 nm; 70 C; 9 GHz; 90 nm; CMOS technology; Intel Pentium 4 processor; Address generation unit; Arithmetic and logic unit; Frequency fast clock; Integer execution core; Leakage power; Low voltage swing circuits; Sparse tree